Teaching As Truth-telling: A Demythologising Pedagogy for the Australian Frontier Wars - Bedford, Alison; Wall, Vince (2020)
Recent scholarship on the history of First Nations Australia is challenging the colonial narrative of Australia’s First Peoples being a nomadic, Neolithic culture. The huge popularity of Bruce Pascoe’s Dark Emu is just one small example of the ways in which Australians are now reassessing the validity of our foundational myth of Europeans bringing ‘civilisation’ to an otherwise ‘uncivilised’ people. This has particular relevance in the state of Queensland, which is in the midst of implementing the most significant overhaul of curriculum undertaken in the last 40 years. The previous senior syllabuses for Ancient and Modern History reflect millennial attitudes to First Nations history, with the 2004 Ancient History syllabus engaging with First Nations Archaeology and the Modern History syllabus looking at the First Nations civil rights movement. The new 2019 syllabuses provide an insight into how attitudes towards and understandings of First Nations history have shifted in the last two decades, with the addition of a dedicated topic on the Frontier Wars added to the Modern History syllabus and the framing of First Nations history significantly revisited to place much more emphasis on the value and ongoing legacy and contributions of First Nations knowledges. This article explores what this means for both secondary History students and teachers, and argues that particularly in teaching the Frontier Wars, there is a need for a new pedagogical framework that reflects and explores our shifting attitudes: from foundation myths to an exploration of our nation’s foundational truths.